Elbow rotation affects the accuracy of rotational formulas: validation of a modified method - Yong Liu; Xiaoju Liang; Jianping Sun; Jining Qu; Bohai Qi; Yating Yang; Qiang Jie (BMC Musculoskeletal Disorders)
Abstract Background Supracondylar humerus fractures (SCHFs) are the most common elbow fractures in children and are typically treated with closed reduction and Kirschner pin fixation. However, varying degrees of residual rotational displacement may remain after closed reduction. Several methods exist to assess rotational displacement, but none account for the effect of elbow rotation on the results. We hypothesize that the accuracy of the primitive rotational calculation formula (PRCF) decreases as elbow rotation increases and propose a modified rotational calculation formula (MRCF). This study aims to investigate the impact of elbow rotation on PRCF and validate the reliability of MRCF. Methods Mimics software was used to reconstruct the distal humerus in a child and create a transverse SCHF, which was then subjected to X-ray fluoroscopy simulation. Axial rotational displacement was simulated in 5° increments, from 0° to 45°. Internal and external elbow rotations were simulated by adjusting the “LAO” and “RAO” angles. Five physicians measured and calculated displacement using both the primitive and modified rotational calculation formulas. Results The PRCF method showed an average error of 17.98° ± 12.31° with a maximum error of 46.46%. Additionally, 13% of measurements had an error under 3°, and 29% had an error under 10°. With MRCF, the mean error for internal rotation was 2.04° ± 1.67°, with a maximum of 6.09%; 68% of cases had an error under 3° and 94% under 5%. For external rotation, the mean error was 2.74° ± 2.66°, with a maximum of 8.29%; 57% of cases had an error under 3° and 98% under 8°. Intraclass correlation coefficients for the five physicians were 0.966 for internal rotation and 0.989 for external rotation. Conclusions This study demonstrates that the accuracy of PRCF decreases as elbow rotation increases, supporting our hypothesis. MRCF effectively addresses the limitations of PRCF and provides stable, accurate measurements of rotational displacement even with varying elbow rotations. Accurate assessment of rotational displacement in the horizontal plane is essential to understanding the relationship between residual rotational displacement and SCHF prognosis. MRCF will play a critical role in this process.